THE IMPLEMENTATION OF 7Ps EDUCATION MARKETING MIX IN EARLY CHILDHOOD EDUCATION INSTITUTION - Siti Nor Asiah; Rahmat Soe'oed; Hasbi Sjamsir (Faculty of Teacher Training and Education, Mulawarman University, 2022)
The 7Ps of education Marketing Mix is an educational marketing mix that can directly promote an educational institution consisting of its components, namely Product, Price, Place, Promotion, People, Process, and Physical Environment components. The purpose of the study is to describe the implementation of marketing using the 7Ps Education Marketing Mix in early childhood education institutions. A qualitative approach with a case study design was used as an approach in this research. Some data were collected using the process of observation, interviews, and documentation. Some data which were obtained from the data collection process then checked for correctness, suitability, and reliability through a triangulation process, and triangulation of methods and sources was used in this study. Some data which got from interviews were triangulated with data from documents and observations. In addition, some data from interviews of one respondent were also checked against other respondents and then concluded. The results of the study can be concluded that the marketing strategy for some components of; Product consisted of a history/overview of the institution, vision and mission, curriculum, implementation of learning, learning technology, school culture, student quality, institutional management, and educational programs. In terms of the aspect of price consisted of funding sources, such as costs to improve quality development, student administration, and student fees. The aspect of place consisted of facilities & infrastructure, learning equipment, game equipment, strategic location, school environment, and public transportation. The promotion consisted of print media, electronic media, social media, participating in events, circular letters, and discounts. People consisted of educators & education staff, strategic partners, organizational culture, and excellent service. The process consisted of public services, learning activities, and administrative activities. The physical environment consisted of school assets, buildings, and school facilities. The benefits of using the 7Ps Education Marketing Mix are as follows: the marketing process done by PAUD institution could be achieved with maximum results, simplifying and unifying various marketing activities into one activity so that marketing is easier to do and manage, limited resources could be used as effectively as possible, could divide some appropriate and balanced marketing tasks, could allocate responsibility to each person which based on the tasks and abilities possessed, facilitated the allocation of costs.